Sensitivity Analysis for Nonlinear Set-Valued Variational Equations in Banach Framework. (20th October 2013) - Farajzadeh, A.; Salahuddin,
Abstract : The main purpose of this paper is to study the sensitivity analysis for nonlinear set-valued variational equations based on ( A, η ) -resolvent operator technique. The obtained results encompass a broad model of results.